Βιομηχανική Οργάνωση & Οικονομική των Δικτύων (2023-01-19-18:40:05) / Μέρος 1 / Προγραμματισμένη Μετάδοση μαθήματος - Λιωνής Νικόλαος (ΕΘΝΙΚΟ ΚΑΙ ΚΑΠΟΔΙΣΤΡΙΑΚΟ ΠΑΝΕΠΙΣΤΗΜΙΟ ΑΘΗΝΩΝ, 2023)
Προγραμματισμένη Μετάδοση μαθήματος: . . . . . . . . . . You You You You You You You You You You You You You You You You You You You You You Can I give it to you? Thank you, you're welcome. I'm going to see if there's room for me to tell you. It's quite a touch. Do you like it? Yes, I do like it. Do you mind if I give it to you? It's OK, it's OK, it's OK, it's OK. It's OK, it's OK, it's OK. It's OK, it's OK. It's OK, it's OK. It's OK. It's OK, it's OK, it's OK. It's OK, it's OK, it's OK. I think it's OK, it's OK. You told me. No, no. You told me to give it to you. Who told me? Well, Aria told me. It's OK. Where did you put it? Where did you put it? I think it's OK, Giorgoudi. I'm going to tell you. It's OK, it's OK. Is there another group? No. Why? Why is there another group? I don't understand. What group are we talking about? Katis and Giorgoudi. Who are they? Oh, OK. How many people were there? I mean, how many people were there? I don't know. Nine people. I don't know how many people were there. Did you leave? I went to Google. Oh. All of them. I was there too. Will it be finished? It hasn't started yet. I was wondering what I was going to do with the presentation. Well. Durable goods. Yes. In fact, the discussion is a step further in the logic of differentiation, if you will. You will see. But in the essence of the economic logic, the lifetime of a product has to do with its quality. In other words, if we remember the logic of differentiation, where you distinguish different characteristics, the quality, it could be one of these characteristics, the quality, with the sense of endurance and the function of the lifetime of a product. Obviously, the basis for a company is to provide usefulness for a certain period of time. So, the meaning of a product's lifetime is not how long it can last. It is to provide usefulness to the consumer. This is the essence. And there is, after this axis, a lot of discussion that changes the logic of the market, of equilibrium, and, obviously, changes the strategy of the business. And this is what we are interested in. Here we will discuss and focus. We do not have a single service in this category. How can the service have a duration? I don't know. What is the basis of service? It depends on the security of the customer. The service is what is consumed, and therefore provides usefulness a certain period of time. I mean, there is no logic in the given time when the exchange takes place. Because, to be precise, we are going to the time when the exchange takes place. But he is talking about the insurance, because the payment is not taken at that time, probably. Why? No, that's exactly how insurance works. I have paid insurance for a month. So, this month that I have paid the insurance, I will enjoy the utility of being insured. The exact meaning is that, if I stop paying the insurance, I will enjoy the utility of the service. That's it. I mean, I will pay everything in front of me. I will not pay it in a day. Ok, this has to do with the subject of payment. It is a financial matter. It is a logistical matter. So, it is not clear to me what the purpose of the service is. Yes, because the service has this characteristic. The characteristic of the service is that it understands the time of the exchange. It cannot be saved. And there is no return to the service. I bought insurance, I bought the service of a lawyer, if you support me in a case. I bought the service of a mechanic to build me a car. That's it. When the service is supplied, I will enjoy at the same time the utility of the insurance. But what is Abtoleasing? We will see. Abtoleasing is a game of strategic optimization. In essence. It is one of the basic issues that creates the duration of life in a product, in a product. In other words, in continuation of what you have mentioned, we have different duration of life in the products. Products that have a different lifetime, a different logic in the sense that their value is reduced over time, in terms of profitability. For example, tools, diamonds. It is like that. It does not change. We built this wall with tools. Finally, this is there. The diamond will remain for millions of years. It does not change. And there are other products, but the characteristics are all the common types of goods. White devices, telephonic devices, computers, mobile phones. They have a duration of life. Which may be 1-2-3-5 years. Until a time comes when the device is broken. Are we talking about this time? Or are we talking about how people spend their 5 years in the wall? They can't stand it. They take it as life. What can't they stand? They take the useful life time, which is this. How useful it is. Or the real life time, that it will last for 5 years. We say that in 3 years it will last so much, more than technology, that nobody can keep it for 3 years. So your life time is 3 years. But the real life time is maybe 8 years. It will last for 8 years. Keep this observation. Because as we will see, this is exactly what we are discussing. This is the strategic management of the lifetime of a product. Therefore, if we talk about the lifetime of a product, it is the same as buying a refrigerator and having it at home. You buy it, you turn it on, and it keeps doing its job. It could be the same. You buy a mobile phone, it could work with a computer, with a mobile phone. You buy a mobile phone and it keeps doing its job. That's it. You buy a computer and it keeps doing its job. Therefore, you don't need to buy this story again. The lifetime of a product is the same. And this is essentially the second element, which is here as a basic statistic, that there is an internal competition, intra-brand competition, within the time. When I say internal competition, the company that produces a product that has a lifetime, let's say a refrigerator, LG Millet or the company Millet, sold a refrigerator today and it competes with itself within the time. Why? Because if it sells today, it won't sell tomorrow. I have a refrigerator at home and in the oven for 15 years. I went to LG to buy a refrigerator once, and I didn't go again. In essence, the company that sold it to me didn't have anyone else in the world to produce a refrigerator. That's not the competition. If it sells today, it won't sell again for the next 10 years. What does this mean? It means that it won't have revenue from the consumers. In contrast with cars. If BMW sells me a car today, it won't sell tomorrow, in the same sense. So there is, and see how it changes, if you can think about it a little, the reality of the market. If we ask you that there are 10 companies that compete, making a refrigerator and selling a refrigerator today, these 10 companies compete with the same 10 companies of the previous year, for how many years does a refrigerator last? If a refrigerator lasts for 10 or 15 years, these 10 companies compete with 10 companies for 15 years. In other words, we are talking about a geometrically larger competition of competitors. Another characteristic that completely differentiates the durable goods market compared to other products, which we buy, we consume, we buy toothpaste, it's over in a month, we go to the supermarket to buy again, we buy chicken, we go again to buy again, and so on, we return the consumers to the market. So the first big issue is this internal competition within the same company, you compete with yourself, within the time, with everyone else. And the second, and the logic of the discrimination of prices within the time. What we talked about all the discussion about discrimination of prices, first degree, second degree, third degree of discrimination of prices, and various strategies there, we saw this in a period, what do I do to the consumer and how do I manage my payments strategically, how do I maximize my income and my profits. This is what I do within the time. But if we change the point of view and we don't see the consumers today, we see the consumers within the time, the consumers today, tomorrow, the day after tomorrow, the day after tomorrow, how do I manage my payments strategically within the time? And how can I make a distinction between first degree, second degree, third degree, and so on, within the time. So that I can maximize my income. A point on the subject of discrimination. Here opens another aspect of which we will discuss. It is the strategic reaction of the consumers on the subject of discrimination. That is, when we say, until now, in the discussion of discrimination of prices, the girls will pay this much, the boys will pay that much. So we had two different prices. If we take this into the time and say, those who will pay today will pay this much, and those who will buy in time will pay this much. Different prices, different prices. Then the consumer's logic comes in, strategically, to choose which price he will pay. If I will buy today or I will wait to buy tomorrow. Which again is a strategic interaction between the business and the consumer on the subject of discrimination of prices. These two are the crucial issues that shape the economic logic, the economic balance on the basis of discrimination of the product. Let's look at them in more detail. Starting with the discrimination of prices. In essence, again, we are discussing to try strategically, as an initiative, to make use of various facilities to pay for, which consumers and general customers may have. To separate into groups, into groups, the most likely answer, and to make use of the different facilities that each group may have. One scenario is something that we have discussed so far. Groups of consumers with different demand flexibility. This could be exactly the same discussion in time. That there may be a group of consumers that have less demand flexibility and another group that have more demand flexibility. Different prices for each group. If this is in time, in essence, if consumers, if the first period that I and many others discussed, consumers that have demand flexibility, that need the product more than we do, in the second period I can reduce my price to make use of the other group of consumers that have more demand flexibility. In other words, the only discussion that we have had so far we will return to in time. Because there is no alternative. Let's talk about demand flexibility. In essence, this is the Kreml Scheming. This is the Kreml Scheming. The initial demand, the initial group, the first group has a demand for flexibility. So I consider them higher. In the second period, I try to approach consumers that have a more flexible demand. What is the Kreml Scheming? I take the balance sheet of the market. I express if I make a mistake, the Kreml Scheming and its return. So I take the balance sheet of the market. How? I take the one that has a flexible demand, and then, after I cover this group, I take the balance sheet of the market and go to the next group that has a lower demand. We usually discuss the Kreml Scheming, which is the price difference in time, and we are looking for new products. There is a group, or a gadget, that wants to have the latest technology. They have advanced it. They have the pre-order. If they pay for it, they have to go out. Let's hear some other examples. The pre-order is a pre-order. Do you pre-order it or do you just pre-order it? Is there a way to pre-order it without paying? In technology, it is very expensive. They go out, pay, and learn. They pre-order the iPhone, pre-order the iPhone, pre-order the time to register, pre-order the time to... Sorry. What is this? I don't know, it's new to me. No, it's not new to me. It's new to me because of the strategic vision of the business in what we have discussed so far. Not necessarily here, but in the rest of the world. Basically, based on recognition. At the end of the day. What is this thing that you call a pre-order? I don't care if I pay in advance. I pre-order it. What is this? I will release the iPhone 15... I don't know if it's the 14 now. I will release the iPhone 15 on June 1st. You can pre-order it as an official product. What is this? Sorry? What is this? What is the business doing with this pre-order? It's just a pre-order. As long as you do it, it's not a problem. Yes, as long as you do it. As long as you do it. As long as you do it. As long as you do it. As long as you do it. But when it comes to the pre-order, what were the criteria? What? The criteria in science. The criteria are the prerequisites. The prerequisites. In the second degree. First and second degree. Where should I start? I am so serious. Be good consumers. If at least this comes out of these discussions, you will have some benefit. What were we saying? That the problem, to a third degree I remember, was that it was a little girl's market. So there I have a noticeable feature to make money in science. In the second degree. I know that some people want, they are fanatics to buy the iPhone 15 first. For samples, because they like technology, for various reasons. I know them, and I don't know what is in my population, the fanatics who will buy it. I know some people who will buy it at some point, it depends on the price, it depends on other things. And I want to separate these two groups. To do this, you have to have the same issue. It is elastic and elastic demand, these two groups. Simple. What is the problem of management? I don't know what is in which group, and how many are in each group. When the company goes out and makes you a marketing, a promo. It tells you that we have announced the group. Ah, hello. It comes, not only it announces in which group, like the... I don't say, I'm sorry. You go and declare that I will pay as much as... I am in the group that has elastic demand. So I will pay as much as your new product. And you give it what you give it. Apart from that, that is, it determines, by yourself you go and declare, what I said, the self-select then, that you make the menu, you choose two packages, and everyone goes and chooses the package they want. I didn't say that. Here. In time. If you see it in technology. It makes you a promo, let's say, I will make this, it will be like this. I will put two stars and I will make the new iPhone 15. It offers you with a marketing that will come out then. And you go and declare by yourself that I belong to this group. What you give is the elastic demand. And you give it everything. Because they didn't announce, I think, in general, that I will sell it to you on June 1, 1000 euros. Slowly they announce it. They say, I will release the new iPhone, it will be released on the 23rd. It will be released on the 1st of June. It will have this and this and this. You make a pre-order and declare. And you give the demand, exactly. That is, from all these types, that I don't know how many are, and in which group they belong, from my 100 national clients, 50 come and tell me that they will buy it. And in fact, with what they tell me, I can make an estimate of the demand, of this elasticity and non-elasticity, and I can go and declare as much as I can. Highly, obviously. That is, you give it whatever information it has, to make a part of the competition, which you have to communicate. And the buyer here feels happy that I was the first to enter the list, to get the iPhone first. And he is happy that you have put, let's say, your neck on my neck, that he will beat you, as far as your testimony and my claim are concerned. But does he want it? Does he want it? Immediately? In a way. So, they come here, to collect exactly the information that they don't have. And in this way, they come and declare exactly the demand. And if you collect, let's say, the data of their total consumption, you have made an estimate of your demand. And if you put even more than that, if you put the construction of the Scythian economy, that you already have their characteristic consumption, because they are new, some of them will be new customers, they have not been bought, they have not been used historically. If they are from your clientele, that you know, that you have been using for 10 years, since you started with the iPhone 1, I don't know, since 2015, and they declare it again, you have a historical consumption. Right? That is, you have determined exactly how much you can pay. So you can make the estimate of the demand, or you can hide it here. You can hide it, in the final estimate. So that's what we do. Now, the pre-payment is again logistical. That is, as is the trust, that I buy something and I will pay it with trust, I will pay it after 1, 2, 3 months, let's say, with my credit card. So, the pre-payment is again logistical. We put a financial savings on top, it has this importance here, but we do not put the pre-payment here, in the financial exchange of the money, we put it in the transfer of the information. What happens in most of these new technology products? If the iPhone 15 comes out, I don't know, it will be paid 2,000 euros, I don't know, 1,500 as it is now, the first year, the second year, it will be paid 1,000 euros, the third year, it will be paid 1,700 euros. Or in all computers, one computer at the moment, I don't know, which is 16 RAM, i7 and 512 SSD, it is at 1,300, right? 8 RAM with i5, it has fallen to 800, it is 1,000, that is, it has a certain value, if you notice it, it has a certain evolution. Whatever you take today at 1,300, in a year it will be 1,000, it will have fallen 300. There is such a law, for example, which is exactly this. Those who have a need, pay exactly the first year, those who can, wait, they will pay less. The opposite of the Crim Scheme is the Penetration Pricing, which in essence we are discussing for opposite elasticities, because first of all you have the elastic demand, so a low price, and in the second year you have the elastic demand, the high demand, in essence, the low price to enter the market, and once you enter the market, remember the switching boards, you start to raise your price, in the second year, in the third year, and after you have started to enter the market, you are frozen in the market, you are frozen by your customers, you have a monopoly right over the market. In the peak load, this is what we will see, peak load pricing, the circular demand, at different times, where the prices are different, depending on the circular demand, but this is theoretically a time duration of the peak load per year. Tourism, a hotel, winter accommodation, you will find it exactly in the peak load, in the winter, and in the summer, cheaply, and affordable for hotels in the summer, you will find it cheaply in the summer, and cheaply, in the off-season, which has to do with this kind of logic, again. Ok. Here I start, I emphasize this discussion, until now, we had how to behave, how to choose the difference only in time. But if we put into this logic the reaction of consumers, that is, that consumers, perhaps, realize that I can buy today, but I can wait for tomorrow, which I will buy at another price, because there is a difference only in time, it is a strategic behavior of consumers. This is what I now put into the discussion, that how to make a conclusion, if it is important, in any case, how does the logic of strategic of consumers matter. What is the basic logic that consumers express expectations. So, the expectation is that I want to buy a new phone, I want to change my phone, I want to buy now, ok, the high-end phone, so I wait for the prices to drop so I can buy tomorrow. I want to change my computer, and I will wait for the prices to drop a few more months for the prices to drop and I will buy tomorrow. Or I can say that I can have expectations that in one day the prices will go up, so I will buy now, although I have no need for it. But because I know that in the second year the prices will go up, I will buy it I would like to say a few words about what I have in front of me. Here we have the legacy of Kojic, or Koj Conjecture. I would like to say that the duration of life in a product and the expectations that consumers may have, and the expectations that consumers may have, affect the monopoly. And they may disappear. In other words, even if we are a monopoly, which produces, we buy some duration of life, my followers will suddenly start to behave strategically, creating expectations for what we will do in our time. This may lead us to the extreme scenario of not having any monopoly right, even though we are the only ones who make an agreement, as the agreement is made by the consumer. That's why it says, a good impression. What we have said is that you may be under a situation in time, that is, you are competing with yourself. That's where the authority of this discussion comes from. So, what I am selling today is competing with what I will sell tomorrow. So, I work in a monopoly. Obviously, all of this is generally accepted in monopoly markets, but the power of the monopoly becomes weaker. Obviously, when you have a good competition, you will have even more power in the market. So, there is no point in understanding the idea that you have it in the monopoly model, but it is valid in general. And what I note is that within this logic of the lifetime of the product, a non-intentional behavior of the monopoly is born to change its value. This is my model, I will go geometrically so that we do not mix too much with mathematics. Perfect competition, a very well-established model of perfect competition. Demand and supply. In terms of supply, a zero margin. So, this is the competitive equilibrium here. This is the equilibrium of the monopoly, right? Marginal revenue, zero marginal cost. So, at this point, it is the non-marginal revenue and marginal cost. I go to the demand and I determine the profit of the monopoly, which is the Russian area. I am a monopoly. I sell at the monopoly price at this point, at time 1. The product has a lifetime. Or else, it does not have a lifetime. I am a monopoly. I will sell today, I will sell tomorrow. So, I will sell today, I will sell tomorrow. The consumers who buy today will not be able to buy tomorrow. They will not be able to buy tomorrow. In the first year, I sold at this price. I sell at the marginal revenue, marginal cost. And I get these profits. Remember what happens in the monopoly. In essence, I reduce the amount offered in relation to the competition. In order to increase the price in order to maximize the profit. So, I have a reduced surplus consumer, this triangle. And I have a loss of the entire portfolio. Which are the consumers who did not enter the market. They are the consumers who would buy at the end of the competition. They would not buy, because the price would be reduced. But because I make a smaller amount in the first year. In the monopoly. In order to create the artificial reduction of the quantity. And the competition between the consumers. So, we ask to pay more than what we want to buy. This is the loss of the entire portfolio. Which means that all these things, the rules, have not been understood. They did not enter the market. In essence, this is the market demand. Mr. Jordima, what does it mean that I sold in the first year to these consumers? The Q1 unit. These consumers did not buy. Because the price was above the low point at which they would end up. So, it is an unsatisfactory demand. With these data, I am a supporter. I am a supporter. I satisfied some consumers by selling at P1. I will open my shop next year. What will I do? These consumers, who are in this part of the demand, will not come to buy. Because they have already seen the product. These consumers did not come to buy last year. Because the price was very high. So, there is a residual demand. The war demand. What will I do? I create a movement in which I can not resist. To reduce the quantity. To reduce the quantity. In order to satisfy the war demand. Or to sell at the war demand. Since I sold in the first year to those who bought at P1. All these consumers did not buy at the low point. They did not buy at the low point. In the second year, those who have low point will not come again. They will come to their homes. In order to have income at P2. I will either have income at P0 or I will not sell to anyone. If I do not finish the same P1. Or I will say to the consumer. Look, those who did not buy last year. How can I serve them and sell to them? In order to sell to them, I have to reduce the price. So by reducing the price by putting a lower price at P2. I start to satisfy the war demand. Now I have done it more briefly. In the second year, I put the price at P2. So I have two periods. And the price is there. In the first year, I have P1. Profit. In the second year, I have P2 as profit. With the satisfaction of the war demand. And the third year, I have P1 as profit. And so, here is the price difference in the last year. I reduce my price. In order to be able to sell to those who were not satisfied in the first year. I have this momentum. This is the involuntary price discrimination. And if I have not studied it, it will occur to me as a momentum. When I open my store in the second year and I will see that I do not have a customer. This, if we look at it, I did it in two periods. So you can not reduce the price automatically here. You can reduce it here. I will do it in one period. In the third year, here and so on. In the end, you will end up in the middle of the competition price discrimination. But. What are the disadvantages? After all, I know as a consumer now. I turn to the other side. I go to the side of the question. I am a consumer above. So I would buy the first year at P1. After all, I know that in the second year, the monopolist will inevitably have to raise the price to sell. In the P2. Do I have the opportunity to wait? And instead of selling at P1, to sell at P2? I create these expectations. The price will be reduced if I do not go. And you can see that if we do not go and do not buy the first year, the price will inevitably be reduced. If there is a coordinated strategy of consumers who do not buy at this price. At P1. But the business will inevitably raise the price in the second year to be able to sell. This is the strategy based on the expectations.